TELAAH KONSEP PEMBELAJAR SEPANJANG HAYAT DARI SUDUT PANDANG AL-QURAN DAN MERDEKA BELAJAR - Ilun Lailatul Habibah, Lilik Yuni W (PRODI PAI FIK UNIRA MALANG, 2024)
This article discusses the concept of lifelong learning from two perspectives: the context of independent learning and within the teachings of Islam. Lifelong learning emphasizes the importance of learning as a continuous process throughout life, unrestricted by age or location. In the context of Islam, seeking knowledge is an obligation for every Muslim, regardless of gender. The Quran and the Hadith of the Prophet Muhammad (peace be upon him) provide glad tidings that every Muslim who seeks knowledge will receive great rewards. Meanwhile, in contemporary education, independent learning supports this idea by building students' capacity to become lifelong learners. Lifelong learning within independent learning is implemented through the Pancasila student profile, aiming to produce students with national identity and global competence. This research uses a quasi-qualitative approach. Data is collected through in-depth interviews, documentation, and observation. The validity of the data is measured using techniques such as checking, credibility, transferability, dependability, and confirmability. Data analysis is conducted in stages and interconnected between data reduction, data display, conclusion drawing, and verification. The results of the study show that the concept of lifelong learning is relevant from both the perspective of contemporary education and within the teachings of Islam. The implementation of independent learning supports this idea by building students' capacity to become lifelong learners, helping them to become independent, flexible, and continually developing individuals.